Evaluation of the Implementation of the Adiwiyata Program in Riau Islands Province - Yunus, Muhammad; Mukhneri Mukhtar; Ma’aruf Akbar (Technium Social Sciences Journal, 2020)
The objective of this research was to evaluate the implementation of the adiwiyata program in Riau Islands Province. This evaluation research used a qualitative method with the CIPP evaluation model. The data in this research was got through observation, in-depth interviews, and documentation studies. Data analysis concluded that: (1) adiwiyata program policies had met standards, (2) adiwiyata program implementation plans did not meet standards, (3) adiwiyata program implementation did not meet standards, and (4) adiwiyata program results were not optimal. The recommendation given is that the implementation of the adiwiyata program in Riau Islands Province runs well, the school is consistent with the predicate adiwiyata school and the assessment of the adiwiyata school is carried out objectively.